1989 as a mimetic revolution: Russia and the challenge of post-communism. (September 2020) - Sakwa, Richard
Various terms have been used to describe the momentous events of 1989, including Jürgen Habermas's 'rectifying revolution, ' and my own notion of 1989 as a type of 'anti-revolution': repudiating not only what had come before, but also denying the political logic of communist power, as well as the emancipatory potential of revolutionary socialism in its entirety. In the event, while the negative agenda of 1989 has been fulfilled, it failed in the end to transcend the political logic of the systems that collapsed at that time. This paper explores the unfulfilled potential of 1989. Finally, 1989 became more of a counter- rather than an anti-revolution, replicating in an inverted form the practices of the mature state socialist regimes. The paucity of institutional and intellectual innovation arising from 1989 is striking. The dominant motif was 'returnism, ' the attempt to join an established enterprise rather than transforming it. Thus, 1989 can be seen as mimetic revolution, in the sense that it emulated systems that were not organically developed in the societies in which they were implanted. For Eastern Europe 'returning' to Europe appeared natural, but for Russia the civilizational challenge of post-communism was of an entirely different order. There could be no return, and instead of a linear transition outlined by the classic transitological literature, Russia's post-communism demonstrated that the history of others could not be mechanically transplanted from one society to another.